2022
DOI: 10.7759/cureus.27876
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain: A Potent Phytomedicine

Abstract: The commercially available protein-digesting enzyme bromelain is derived from the pineapple fruit or stem. Bromelain from fruit and stems are produced in different ways and has varied enzyme compositions. "Bromelain" often refers to the "stem bromelain". Bromelain is a combination of several thiol endopeptidases and others including various protease inhibitors, glucosidase, cellulase, phosphatase, peroxidase, and escharase. Studies conducted in both the lab and on animals show that bromelain has a variety of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 49 publications
0
23
0
3
Order By: Relevance
“…It plays a significant role in the treatment of various skin problems, such as dry skin, acne, and wrinkles. 140 Several investigational studies reported that bromelain acts by selectively digesting the protein layers of dead skin cells, leading to the removal of these layers and promoting the growth of new and younger skin cells. 139 This action is due to the proteolytic activity of bromelain, which breaks down the structural proteins in the epidermis and enhances the removal of dead skin cells.…”
Section: Cosmetic Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…It plays a significant role in the treatment of various skin problems, such as dry skin, acne, and wrinkles. 140 Several investigational studies reported that bromelain acts by selectively digesting the protein layers of dead skin cells, leading to the removal of these layers and promoting the growth of new and younger skin cells. 139 This action is due to the proteolytic activity of bromelain, which breaks down the structural proteins in the epidermis and enhances the removal of dead skin cells.…”
Section: Cosmetic Industrymentioning
confidence: 99%
“…It reduces inflammation, redness, and swelling, making it an ideal ingredient for use in products targeted towards sensitive or acne-prone skin. 140 It also helps to stimulate collagen production, which is essential for maintaining skin elasticity and firmness, making it a popular ingredient in anti-aging creams and serums. 141 Bromelain is often used in conjunction with other ingredients, such as alpha-hydroxy acids (AHAs) or retinol, to enhance its exfoliating and anti-aging effects.…”
Section: Industrial Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit bromelain (E. C 3.4.22.33) has an isoelectric point of 4.6, a molecular weight of 24.5-32 kDa, an optimum pH range of 3-8, and an optimum temperature range of 37-70°C. The optimum pH and temperature range of fruit bromelain are wider compared to stem bromelain [8, [10][11][12][13]. Thus, fruit bromelain obtained from pineapple peel waste was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Bromelain, a crude extract from the pineapple, contains various closely related proteinases. This proteolytic enzyme has demonstrated antioedematous, anti-inflammatory, antithrombotic and fibrinolytic properties when observed in both invivo and in-vitro studies [8][9][10][11][12]. Bromelain also offers a wide range of therapeutic benefits including reversible inhibition of platelet aggregation, angina pectoris, bronchitis, sinusitis, surgical traumas, thrombophlebitis, pyelonephritis and enhanced absorption of antibiotics [6].…”
Section: Introductionmentioning
confidence: 99%